Results of Endovascular Occlusion of Vertebro-Vertebral Arteriovenous Fistulas - Svyrydiuk, Oleh Ye.; Altman, Igor V.; Sereda, Serhii O.; Boyko, Juliia M.; Vyval, Mykola B. (Ukrainian Journal of Cardiovascular Surgery, 2025)
Aim. To analyze the results of endovascular treatment of vertebro-vertebral arteriovenous fistulas (VV-AVFs). Materials and Methods. A retrospective analysis was performed on the treatment outcomes of 291 patients with arteriovenous fistulas (AVFs) of various localizations who were treated at the State Institution “Scientific-Practical Center of Endovascular Neuroradiology of the NAMS of Ukraine” between January 2012 and March 2024. All patients underwent endovascular embolization of AVFs and follow-up cerebral angiography (DSA) at different intervals, ranging from 1 to 12 years. Five patients (1.7 %) were diagnosed with VV-AVFs. Patient age ranged from 48 to 61 years (mean: 54 years). The fistulas were most commonly located in the V2 segment of the vertebral artery. Typical clinical manifestations included a pulsatile mass or bruit, often accompanied by neck pain or upper-limb paresthesia. Regarding etiology, three cases were spontaneous, and two were traumatic in origin. Results. Five embolization sessions were performed in five patients with VV-AVFs (one per patient). Detachable coils were used in all procedures, and n-butyl cyanoacrylate (nBCA) in four. No procedural complications occurred. Complete occlusion of the fistulous connection was achieved in four cases. In one patient, a residual low-flow shunt from the external carotid artery territory was identified, for which conservative observation was chosen. No patient experienced neurological deterioration after embolization. Postoperative recovery was uneventful, and symptomatic improvement was noted in all patients upon discharge. The mean hospital stay was 5.6 days. All patients were discharged with modified Rankin Scale (mRS) scores of 0-1. Follow-up angiography was available in three patients and revealed no signs of recanalization. Conclusions. Endovascular exclusion of vertebro-vertebral arteriovenous fistulas is a modern, minimally invasive, and effective treatment technique that prevents serious complications and improves the quality of life in affected patients. However, the decision to perform the procedure should be made individually, taking into account the patient’s condition, as well as the location, size, and hemodynamic characteristics of the fistula.